GAMBARAN PELAKSANAAN PROGRAM TUBERKULOSIS DI PUSKESMAS KEBON HANDIL KOTA JAMBI TAHUN 2022 - Utami, Selia Tiara Putri (LPPM Universitas Jambi, 2023)
ABSTRACTBackground: Pulmonary tuberculosis (pulmonary TB) is an infectious disease, which primarily affects the lungparenchyma. The name Tuberculosis comes from a tubercle which means a small, hard bulge that forms when theimmune system builds a wall around the bacteria in the lungs. Pulmonary tuberculosis is chronic and ischaracterized by the formation of granulomas and causes tissue necrosis. Pulmonary TB can be transmitted throughthe air, when someone with active TB in the lungs coughs, sneezes or talks.Method: This final project was made based on data found in the puskesmas. After the data collection process iscomplete, the data is processed using SPSS and analyzed using the problem-solving cycle method. The cyclestarts from identifying problems with brainstorming, after collecting several problems that exist in the lowachievement of monitoring toddler growth at the Kebun Handil Health Center, then these problems are confirmedwith primary or secondary data.Conclusion: Priority issues related to the description of the TB Implementation Program are still lacking, namelythe achievement of the TB case detection target in 2022 has not been achieved, namely only 23.8%. The causeof the dominant problem is that people's knowledge about TB is still low. The chosen problem solution is Retrainingfor the active participation of all health center staff outside and inside the building related to counseling andeducation about TB to all Kebon Handil people. The lack of public knowledge apart from oneself is also determinedby the information received, increasing human resources is one of the ways chosen to improve this condition.Keywords: Tuberculosis